Communicating about science and engineering practices and the nature of science: An exploration of American Sign Language resources. Issue 6 (6th January 2020) - Enderle, Patrick; Cohen, Scott; Scott, Jessica
Abstract: Science classrooms have been demonstrated to be educational contexts with unique and challenging language demands. Enhanced cognitive and linguistic demands arising from an emphasis on the science and engineering practices (SEPs) and the nature of science (NOS) in the Next Generation Science Standards warrant consideration of how to support students with different language abilities. Deaf and Hard of Hearing (DHH) students must negotiate multiple languages in the science classroom, including academic science vocabulary, written English, and spoken American Sign Language (ASL). However, science‐specific ASL vocabulary is rather limited, and current development efforts mostly focus on developing signs for more traditional content vocabulary. Yet, effective science instruction for DHH students must also provide them opportunities to engage in and communicate about the NOS and the functions of the SEPs. The current study explores the availability of such ASL resources across a body of science‐specific resources available for teachers of DHH students. Reviewing a body of publicly available resources, researchers identified a small list of 21 ASL signs that are common across multiple resources. These signs, and the larger data set, were reviewed to identify trends and patterns across them and how well they communicate scientific meanings for NOS and the SEPs. Issues that emerged and classroom implications are discussed.